Emerging role of the TCA cycle and its metabolites in lung disease - Lu, Xinan; Zhang, Aijun; Wang, Huaying; Xu, Xinjia; Chen, Liping; Luo, Lingfang (Frontiers in Physiology, 2025)
The TCA cycle is a central pathway for oxidative phosphorylation in eukaryotic mitochondria, plays a role in energy production and biosynthesis, and can alter cellular function in a variety of ways. As our understanding of the TCA cycle has improved, there is increasing evidence that it is inextricably linked to lung disease. This article summarizes the relationship between the TCA cycle and different types of lung disease and focuses on the specific mechanisms by which the TCA cycle and its intermediate metabolites influence lung disease progression.